Analysis of development and effects of electronic trade in Serbia based on SF-TOPSIS and TOPSIS methods - Lukić, Radojko (Anali Ekonomskog fakulteta u Subotici, 2023)
There is no doubt that today the issue of measuring and analyzing the dynamics of development and the effects of electronic commerce in each country is very current, significant and complex. This means in Serbia as well. Based on that, this paper measures and analyzes the dynamics of development and the effects of electronic commerce in Serbia using SF-TOPSIS and the classic TOPSIS method. In the observed time period 2017 - 2021, according to the empirical results obtained based on the SF-TOPSIS method, the largest number of trading companies in Serbia with the introduction of electronic business (information and communication technology) and electronic traffic was in 2017. They are in order: 2021, 2018 , 2019 and 2020. According to the empirical results obtained using the classic TOPSIS method in the period 2017-2021, the largest number of trading companies in Serbia with the introduction of electronic business and electronic traffic was recorded in 2019. They are in order: 2020, 2021, 2017 and 2018. Recently, the information system of trade in Serbia has been significantly improved. This had a positive impact on its overall performance, given that the digitalization of the entire business is one of the critical factors of business success. It significantly mitigated the negative effects of the Covid-19 pandemic. The factors of digitalization of the entire business of trade in Serbia are the global trend and needs, the development of modern information and communication technology and the possibilities of application in all segments of trade, the economic climate, financial opportunities, the influx of foreign retail chains, the development of multi-channel sales - classic and electronic stores, the business of non -stop without time and geographical barriers, etc.